2022
DOI: 10.1039/d2nj02644a
|View full text |Cite
|
Sign up to set email alerts
|

Detection of chymotrypsin using a peptide sensor based on graphene oxide modified with sulfhydryl groups and gold nanoparticles

Abstract: In this study, GO modified with sulfhydryl group was prepared by thiolation on the surface of GO, which makes a meaningful material. GO with sulfhydryl group combined with gold nanoparticles,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As shown in Figure 1a, several characteristic peaks of GO were observed in the FT-IR spectrum including the peaks at 3386, 1718, 1618, and 1050 cm −1 , due to O-H stretching vibration, C=O stretching vibration, C-OH stretching vibration, and C-O stretching vibration, respectively. This showed that GO was successfully synthesized [27]. Figure 1b shows the SEM of GO.…”
Section: Sensitivity For Thrombin Detection Using a Covalent Linking ...mentioning
confidence: 81%
“…As shown in Figure 1a, several characteristic peaks of GO were observed in the FT-IR spectrum including the peaks at 3386, 1718, 1618, and 1050 cm −1 , due to O-H stretching vibration, C=O stretching vibration, C-OH stretching vibration, and C-O stretching vibration, respectively. This showed that GO was successfully synthesized [27]. Figure 1b shows the SEM of GO.…”
Section: Sensitivity For Thrombin Detection Using a Covalent Linking ...mentioning
confidence: 81%
“…After peptide breakdown by chymotrypsin, AuNPs were more tightly bound to GO, and absorbance was improved. This method achieved a low LOD of 0.25 pg/mL [198].…”
Section: Detection Of Chymotrypsinmentioning
confidence: 91%